Penguatan Nutriforce Melalui Pelatihan Konten Media Untuk Branding dan Promosi Pelayanan Konsultasi Gizi - Lironika, Arinda; Rosiana, Nita Maria; Olivia, Zora; Widyawati, Agatha; Adi, Kukuh Prayitnaning (P3M Politeknik Negeri Jember, 2025)
The number of client visits to the Nutrition Care Center (NCC) since it began operating in 2022 has tended to decrease from 110 people to 98 people in 2023. This figure has not reached the target number of visits, even though in 2023 efforts have been made to organize promotional events NCC only carries out offline promotions to attract client visits, so it has not yet reached the wider community.. However, NCC has Nutriforce which can strengthen its potency. This activity aims to increase the number of visits to nutrition consultation services at NCC through branding activities and promotion of nutrition consultation services. This activity was carried out during August 2023, involving 10 people. Activities are divided into preparation, implementation, and monitoring and evaluation stages. The implementation method is FGD, counseling, training and assistance in creating images and videos for social media content for branding and promoting NCC more intensively. The success of the extension activities was evaluated using a pre-test-post-test knowledge questionnaire and then analyzed using a paired T-test. The results show an increase in Nutriforce's knowledge in creating nutritional consultation promotional content. In addition, there are additional promotional videos and images via Instagram social media which are produced every week.